Incorporating other texts: Intertextuality in Malaysian CSR reports - Rajandran, Kumaran (Asociación Europea de Lenguas para Fines Específicos, 2016)
In Malaysia, corporate social responsibility (CSR) is relatively new but corporations have been required to engage in and disclose their CSR. A typical genre for disclosure is CSR reports and these reports often refer to other texts. The article investigates the act of referencing to other texts or intertextuality in Malaysian CSR reports. It creates an archive of CEO Statements and Environment Sections in CSR reports and studies the archive for keywords, which can identify the incorporated texts. The function of these texts is examined in relation to Malaysia’s corporate context. CSR reports contain explicit references to documents (policies, regulations, reports, research, standards) and to individuals/groups (CEOs, stakeholders, expert organizations). The incorporated texts display variation in corporate control, which organizes these texts along an intertextual cline. The cline helps to identify corporate and non-corporate sources among the texts. The selection of incorporated texts may reflect government and stock exchange demands. The texts are not standardized and are relevant for the CSR domain and corporations, where these texts monitor and justify CSR performance. Yet, the incorporated texts may perpetuate inexact reporting because corporations select the texts and the parts of texts to refer to. Since these texts have been employed to scrutinize initiatives and results, CSR reports can claim to represent the “truth” about a corporation’s CSR. Hence, intertextuality serves corporate interests.